2019
DOI: 10.3389/fpsyg.2019.01336
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mindfulness Interventions for Parents on Parenting Stress and Youth Psychological Outcomes: A Systematic Review and Meta-Analysis

Abstract: Background: The psychological well-being of parents and children is compromised in families characterized by greater parenting stress. As parental mindfulness is associated with lower parenting stress, a growing number of studies have investigated whether mindfulness interventions can improve outcomes for families. This systematic review and meta-analysis evaluates the effectiveness of mindfulness interventions for parents, in reducing parenting stress and improving youth psychological outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
135
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(161 citation statements)
references
References 127 publications
(216 reference statements)
19
135
4
3
Order By: Relevance
“…Trials assessing MBPs in nonclinical settings have quickly accumulated in recent years. Systematic reviews have synthesised findings from MBPs from educators [11,12], parents [13], caregivers [14,15], healthcare professionals [16][17][18][19][20][21], athletes [22], working adults [23][24][25][26][27], older adults [28], university students [29][30][31], and the general population [32][33][34][35][36], primarily focusing on wellness and mental health outcomes. Most, but by no means all results favour MBPs over comparison conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Trials assessing MBPs in nonclinical settings have quickly accumulated in recent years. Systematic reviews have synthesised findings from MBPs from educators [11,12], parents [13], caregivers [14,15], healthcare professionals [16][17][18][19][20][21], athletes [22], working adults [23][24][25][26][27], older adults [28], university students [29][30][31], and the general population [32][33][34][35][36], primarily focusing on wellness and mental health outcomes. Most, but by no means all results favour MBPs over comparison conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness interventions for parents have been widely studied over the last years, showing promising results in reducing levels of parental stress (Burgdorf et al 2019). Parents can take part in a mindfulness-based stress reduction training (MBSR) (Kabat-Zinn 1990) to practice mindfulness meditation in general.…”
mentioning
confidence: 99%
“…A MP training specifically aims to help parents cope with, and regulate their parental stress (Bögels et al 2010;Potharst et al 2018b). A systematic review and a recent meta-analysis provided insight in the effectiveness of a MP training and mindfulness interventions for parents of children of different ages and different settings (mental health setting and preventive setting), and showed reduced parental stress and improved child behavioral outcomes (Burgdorf et al 2019;Townshend et al 2016). In addition, a recent study on a MP training specifically designed for mothers with a toddler found improvements in parental stress, mother-toddler interactions, and toddler behavioral problems (Potharst et al 2018b).…”
mentioning
confidence: 99%
“…Mindfulness from the mental health domain has been extensively researched and results reveal it to be beneficial for stress reduction [ 11 , 24 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. For example, a systematic review and meta-analysis of 45 randomized control trials (RCT) revealed that mindfulness mediates the physiological markers of stress, such as cortisol, heart rate, blood pressure, and triglycerides in individuals who practice meditation [ 72 ].…”
Section: Introductionmentioning
confidence: 99%